Wave-induced bedload transport – a study of the southern Baltic coastal zone - Dudkowska, Aleksandra; Gic-Grusza, Gabriela (Geologos, 2017)
The wave-induced bedload transport and spatial distribution of its magnitude in the southern Baltic coastal zone of Poland are estimated. The vicinity of Lubiatowo was selected as a representative part of the Polish coast. It was assumed that transport is a function of shear stress; alternative approaches, based on force balances and discharge relationships, were not considered in the present study. Four models were studied and compared over a wide range of bottom shear stress and wind-wave conditions. The set of models comprises classic theories that assume a simplified influence of turbulence on sediment transport (e.g., advocated by authors such as Du Boys, Meyer-Peter and Müller, Ribberink, Engelund and Hansen). It is shown that these models allow to estimate transport comparable to measured values under similar environmental conditions. A united general model for bedload transport is proposed, and a set of maps of wave bedload transport for various wind conditions in the study area is presented.